(untitled) (International Journal of Innovative Technologies in Economy, 2024)
Since 1994, South Africa has prioritized quality education by ensuring that young learners are taught by qualified teachers. A notable shift has been the inclusion of qualified teachers in Reception year classes. This study investigates the experiences of Level 3 and 4 Bachelor of Education in Foundation Phase student teachers during their practicum in Reception year classrooms and the perspectives of university lecturers who assessed them. Using an experiential learning theoretical framework and a qualitative interpretive research design, data were collected through open-ended questions posed to student teachers. Findings indicate that student teachers had positive experiences, but university lecturers noted that lessons were often teacher-centred, lacking play or inquiry-based methods. Lecturers also highlighted that the Foundation Phase teacher education programme did not adequately support Reception Year teacher development, citing time constraints and insufficient physical space for practical activities. The study recommends re-evaluating the inclusion of Reception year training in the B. Ed Foundation Phase programme and developing an assessment tool to evaluate Grade R student teachers’ planning and presentation skills.